THE INFLUENCE OF SUSTAINABILITY PERFORMANCE ON THE VALUE OF BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ari Kurniawan Putra; Onong Junus; Novaliastuti Masiaga; Julie Abdullah; Saprudin Saprudin (LPPM STIE Muhammadiah Bandung, 2025)
In order to increase your company's value and entice investors, you must ensure that your sustainability performance is maintained by adhering to criteria for environmental performance, social performance, and governance performance. The impact of ESG performance indicators on a company's value is examined in this study using Tobin's q. This study takes a look at one banking firm that is listed on the Indonesia Stock Exchange. It uses a 5-year purposive selection technique. This study analyzed the data utilizing multiple regression analysis using a panel data strategy. Findings indicate that ESG (environmental, social, and governance) performance influences company value. The existing literature on the potential effects of ESG data on investment choices and the optimization of company value is expanded upon by this study. In order for investors to make well-informed choices on which companies to put their money into, this study emphasizes the importance of ESG performance in company operations.